Congener profiles of polychlorinated dibenzo-p-dioxins and polychlorinated dibenzofurans (PCDD/Fs) in sediment, water, and fish at a soil contamination site in Taiwan. Issue 3 (23rd February 2016) - Chang, Hwang-Jen; Lin, Tsair-Fuh; Whang, Liang-Ming; Wu, Yi-Ju
ABSTRACT: The relationship of polychlorinated dibenzo -p- dioxins and polychlorinated dibenzofurans (PCDD/Fs) in sediment, water, and fish was studied for 55 fish farms near a contaminated site in Tainan, Taiwan. Samples were collected from the farms and analyzed for seventeen 2, 3, 7, 8-substituted PCDD/Fs congeners. High correlations were found between PCDD/Fs in water and sediment in regard to both concentration and toxicity (R 2 = 0.933 for concentration and R 2 = 0.832 for toxicity). The congener profiles of the 17 PCDD/Fs in water were similar to those in the sediment. However, the PCDD/Fs congener composition in the fish and fish belly samples were different from those in the sediment and water samples obtained from the same fish farm and were also different among the fish samples. It is thus suggested that the biotic PCDD/Fs distribution is more complex than the abiotic PCDD/Fs distribution. Among the seven factors analyzed, only the lipid percentage presented a relationship with the PCDD/Fs congener composition in the fish and fish bellies. A multiple linear regression of the concentration of each congener in the fish was conducted using the concentration of each congener in the site-matched sediment and the lipid content of the fish as independent variables. The results showed that only seven PCDD/Fs congeners with a lower degree of chlorination, which were 4-6 chlorine substitutes, in the fish presented a significant correlation with the lipid content in the fish and their concentration in sediment (r > 0.65, P < 0.005 for both independent variables). In addition, the octanol-water partition coefficients were not significantly related to this distribution behavior.